Conceptual design of wheelchair for disabled people suffering with tetra phocomelia disease - Ariff, A.F.B.; Omer, H.B.; Javedd, P.M.; Alkbir, M.F.M. (2018)
Providing a wheelchair without a comprehensive support service can be detrimental to user satisfaction and function. Recently, a lot of interest in full-featured wheelchairs in the medical service field and in various other engineering fields including multi-purpose wheelchairs such as houses and shops. This paper deals with the Conceptual design of wheelchair for disabled people Suffering with tetra phocomelia disease. A systematic approach to the overall design process allows designers to better understand the best design concepts of the product. This paper describes the process of manufacturing wheelchairs using stainless steel.